Propagation mechanism of gaseous detonations in annular channels with spiral for acetylene-oxygen mixtures. (15th April 2021) - Yang, Tianwei; Ning, Jianguo; Li, Jian
Highlights: Long smoked foil is obtained to record structures in rough tube by a special design. An abrupt drop in velocity deficit is found mainly occurring in stable mixtures. The effects of obstacle diffraction and cellular instability are distinguished. Detonation limits for velocity discontinuity in rough annular tubes are obtained. Detonation propagation limits in annular and circular rough tubes are compared. Abstract: The propagation mechanism of detonations in the annular channel with a spiral is experimentally studied for an acetylene and oxygen mixture with different levels of argon dilution. Detonation velocity is measured through the placement of regularly spaced photodiodes along the test tube. A high-speed camera is also used to supplement the photodiodes when the luminosity decreases. Smoked foils of long length are inserted into the annular channel to register the cellular structures. The results indicate that the effect of the spiral on detonation propagation highly depends on the intrinsic instability of the detonation. With a decrease in the initial pressure, the propagation changes from spiral-induced multi-head mode to spiral-induced single-head mode and then spiral-induced shock-flame complex mode; then, the propagation fails as the limit is approached. Discontinuities in normalized velocity are found for mixtures with high argon dilution, which indicates the transition from single-head spin to shock-flame complex, as observed from the smoked foils. Such a phenomenon is not observed in cases with an unstable mixture of C2 H2  + 2.5O2 or in cases with large roughness. This is because of the different mechanisms stable and unstable detonations and the corresponding response to the boundary change. The critical width of the annular channel normalized by cell size for the discontinuity is found to slightly larger than 1/ π, which corresponds to the lowest quenching limit in smooth tubes, particularly for stable detonations. The critical diameter normalized by cell size for the discontinuity in the circular tube is almost twice the critical width in the annular channel, equal to the geometrical scaling based on front curvature theory.